Quantitative Structure Property Relationships to Evaluate the Photosensitizing Capability in Porphyrins and Chlorins - Cardenas-Jiron, G; Santander-Nelli, M; Santander-Nelli, M (2011)
The wavelength of the Q band (?Q) of sixteen compounds (porphyrins and chlorins) was related to eight descriptors (aromatic, electrostatic, and reactivity ones) by using quantitative structure property relationships (QSPR). These descriptors were calculated using density functional theory (DFT). No single linear regressions were found. So, our work demonstrates that ?Q does not depend on a unique property; rather it is a multidimensional parameter. From twelve QSPR models obtained, four of them yielded regression coefficients over 0.8. In addition, the ?Q values resulting from our QSPR models are closer to experiment than time dependent-DFT calculated ones. It has been proved the power of QSPR models to reproduce and predict the ?Q values for new porphyrin derivatives with potential capability to be used in Photodynamic Therapy. © 2010 Wiley Periodicals, Inc.